38 From theory to clinical practice: lessons learned from the delivery of a breathlessness support service. Issue 3 (1st September 2018) - Reilly, Charles C; Maddocks, Matthew; Jolley, Caroline J; Moxham, J; Higginson, Irene J
Abstract : Introduction: A single-blind randomised controlled trial demonstrated that an integrated palliative and respiratory care service for patients with advanced disease and chronic breathlessness known as the Breathlessness Support Service (BSS) resulted in improved patient's mastery in the BSS group compared to standard care (mean difference 0·58 95% CI 0·01–1·15 p=0·048; effect size 0·44). 1 Aim: To describe the clinical aspects of delivering the BSS with regards to; referral sources patient characteristics and interventions provided. Method: Secondary data analysis of all patients that were referred to and completed that BSS intervention as part of the delayed intervention model RCT. 1 Results: 105 patients enrolled in the study 86 patients attended the first BSS clinic 75 completed the BSS intervention (two clinic appointments and a physiotherapy-based home visit). 80% of patients had non – malignant disease; respiratory medicine constituted most referrals. The majority (88%) of patients received solely non – pharmacological interventions. 35 (41%) patients reported that the have never accessed Pulmonary Rehabilitation (PR). At the point of discharge the BSS provided on ward referral and/or access to additional services (PR=53% social work=41% palliative care=11%). Conclusions: Majority of referrals were from respiratory medicine and GP practices for patients with chronic breathlessness due to non – malignant disease which highlights the challenges of trying to palliate breathlessness in the generalist setting. The BSS provided patients with access to self-management non – pharmacological interventions delivered by integrated multi-disciplinary team with expertise in breathlessness management which resulted in improved breathlessness mastery. Reference: . Higginson IJ, et al . An integrated palliative and respiratory care service for patients with advanced disease and refractory breathlessness: A randomised controlled trial. The Lancet Respiratory Medicine 2014;2(12):979–987.